2022
DOI: 10.1002/ldr.4488
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate N addition improves soil aggregate stability through AMF and glomalin‐related soil proteins in a semiarid agroecosystem

Abstract: Soil aggregation and structural stability play a crucial role in soil organic carbon (SOC) sequestration. However, the underlying mechanisms of arbuscular mycorrhizal fungi (AMF) and glomalin-related soil protein (GRSP) responses to N addition and their impacts on soil aggregation and organic carbon stability remain unclear. Hence, a 16-year field N addition experiment on winter wheat (Triticum aestivum L.) was conducted to investigate the effects on the stability of soil structure and SOC fractions via AMF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 72 publications
1
6
0
Order By: Relevance
“…Numerous studies have demonstrated a significant increase in the proportion of macroaggregates after vegetation restoration (Wilpiszeski et al 2019; Rong et al 2020; Dong et al 2022a). This occurs because tillage practices break down soil aggregates and remove plant debris from the soil surface, thus inhibiting soil agglomeration (Zhang et al 2022). However, after restoring vegetation on cropland, human activities no longer destroy the soil structure, so large amounts of litter, root exudates, and dead root inputs are left untouched, which is conducive to the formation of macroaggregates (Six et al 2001; Six et al 2004; Wilpiszeski et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have demonstrated a significant increase in the proportion of macroaggregates after vegetation restoration (Wilpiszeski et al 2019; Rong et al 2020; Dong et al 2022a). This occurs because tillage practices break down soil aggregates and remove plant debris from the soil surface, thus inhibiting soil agglomeration (Zhang et al 2022). However, after restoring vegetation on cropland, human activities no longer destroy the soil structure, so large amounts of litter, root exudates, and dead root inputs are left untouched, which is conducive to the formation of macroaggregates (Six et al 2001; Six et al 2004; Wilpiszeski et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…1). First, during tillage, the remaining crops were removed, resulting in no organic matter being added to the soil (Zhang et al 2022). However, large amounts of roots and litters were input after vegetation restoration (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its inherent stability in the soil means that it does not decompose rapidly, thereby sequestering carbon directly. Additionally, biochar influences the soil's physical and chemical properties, improving soil aggregation and porosity, which indirectly supports the stabilization of additional SOC by enhancing the physical protection of soil organic matter and promoting conditions conducive to increased microbial activity [43]. Manure, derived from animal excreta, often combined with bedding materials, is a traditional soil amendment that supplies not only organic carbon but also nutrients, particularly nitrogen, phosphorus, and potassium.…”
Section: Organic Amendmentsmentioning
confidence: 99%
“…They are well known for assisting host plants with phosphorus uptake (Smith and Read, 2008;Lu et al, 2023), but can also provide other benefits such as protection from pathogens (Cardoso and Kuyper, 2006;Sharma et al, 2023), assistance with the uptake of other nutrients such as nitrogen and copper, and improved water relations (Smith and Read, 2008;Sene et al, 2010;Lu et al, 2023;Sharma et al, 2023). AMF hyphae also play a role in the formation and structural stability of soil aggregates (Zhang et al, 2023) and contribute to the composition of plant community structures (Chen et al, 2023). On the other hand, plant growth promoting rhizobacteria (PGPR), isolated as free-living soil bacteria from the use rhizosphere of plants, can help reduce mineral fertilizer and increase plant growth and yield (Swarnika et al, 2022;Bhanse et al, 2022;Dhawi, 2023).…”
Section: Introductionmentioning
confidence: 99%